Zöld filozófia és fenntarthatóság az oktatásban - Horváth, Péter János (Kultúratudományi Szemle, 2023)
In this study, starting from the social philosophy based on conservative values, I examine some educational philosophy components of sustainability. First, I review the most important fundamental theses of environmental ethics and environmental philosophy in the light of how and in what form these approaches can appear in education. I turn primarily to the work of Roger Scruton, since he is the person most closely associated with the trend of conservative green philosophy. My goal is to show a clear path in terms of more sustainable energy use along the Scruton principles to those generations who will undoubtedly face the sustainability challenges that arise more intensively than the current generations.